Mass Spectrometry Amyloid Typing Is Reproducible across Multiple Organ Sites - Holub, Dusan; Flodrova, Pavla; Pika, Tomas; Flodr, Patrik; Hajduch, Marian; Dzubak, Petr (BioMed research international, 2019)
We have determined patient's amyloid subtype through immunohistochemical and proteomic analyses of formalin-fixed, paraffin-embedded (FFPE) tissue samples from two affected organs per patient. Amyloid typing, via immunohistochemistry (IHC) and laser microdissection followed by the combination of liquid chromatography with mass spectrometry (LMD-LC-MS), was performed using tissue samples of the human heart, liver, kidney, tongue, and small intestine from 11 patients, and the results were compared with clinical data. LMD-LC-MS correctly typed AL amyloidosis in all 22 FFPE tissue samples despite tissue origin. In contrast, IHC was successful only in the analysis of eight FFPE tissue samples with differences between the examined organs. In the majority of LMD-LC-MS typed samples, the level of IHC staining intensity for transthyretin and serum amyloid A was the same as that for Ig κ and Ig λ antibodies, suggesting low Ig κ or Ig λ antibodies reactivity and the additional antibody clones were essential for correct typing. Both methods used in the study were found to be suitable for amyloid typing, although LMD-LC-MS yielded more promising results than IHC.
Keywords: Aged; Chromatography, Liquid; amyloid; Aged, 80 and over; Amyloid; proteomika; protilátky; lidé; lidé středního věku; senioři; ženské pohlaví; Proteomics; Liver; játra; amyloidóza; zalévání tkání do parafínu; Tissue Distribution; Female; mužské pohlaví; Kidney; Mass Spectrometry; tenké střevo; ledviny; Myocardium; Middle Aged; hmotnostní spektrometrie; myokard; senioři nad 80 let; Formaldehyde; Paraffin Embedding; tkáňová distribuce; Humans; formaldehyd; Male; chromatografie kapalinová; Amyloidosis; jazyk; Antibodies; Tongue; Intestine, Small